An analysis of the shear‐transfer actions in reinforced concrete members without transverse reinforcement based on refined experimental measurements. (30th November 2017) - Cavagnis, Francesco; Fernández Ruiz, Miguel; Muttoni, Aurelio
Abstract : A traditional difficulty in the understanding of the role of the various shear‐transfer actions in members without transverse reinforcement has been a lack of detailed measurements on the development of shear cracking and their associated kinematics during the process of failure. In this paper, this issue is addressed on the basis of an experimental program on 20 beams investigated by means of digital image correlation. The measurements are shown to allow a clear understanding of the mechanisms leading to shear failure and their evolution (transfer of forces between the various potential shear‐carrying actions) during the loading process. The amount of shear carried by the various potential shear‐transfer actions is estimated for varying levels of load accounting for the cracking pattern and actual kinematics on the basis of fundamental constitutive laws for concrete and steel. The results are shown to be consistent and provide a rational basis for the understanding of the phenomenon of shear transfer in reinforced concrete members without transverse reinforcement.